Creative design teaching-learning methods: A reflection from the professors (2013)
The main purpose of this article is to identify teaching and learning strategies that enhance creativity and decision making in Design Education. The experiences of the instructors are used as the main input to the process. Each instructor in the Department of Design was interviewed to detect his/her needs in their own teaching activities. All of the instructors who were interviewed expressed their desire to learn and apply diverse educational strategies. We then sent out a survey to each one of them and asked them to describe their best learning strategies to share them with their colleagues. We found that their preferred strategies were short duration exercises where the student makes design-related decisions through the application of the concepts he/she has learned. These exercises foster the ability of rapid decision-making and effective communication on a short time frame. The results of this process call for improvements in the strategies that were presented, to promote learning activities that contribute in the development of higher-level cognitive skills and improve the performance of designers in their work environment.